How Neutrophils Meet Their End. Issue 6 (June 2020) - Lawrence, Shelley M.; Corriden, Ross; Nizet, Victor
Abstract : Neutrophil death can transpire via diverse pathways and is regulated by interactions with commensal and pathogenic microorganisms, environmental exposures, and cell age. At steady state, neutrophil turnover and replenishment are continually maintained via a delicate balance between host-mediated responses and microbial forces. Disruptions in this equilibrium directly impact neutrophil numbers in circulation, cell trafficking, antimicrobial defenses, and host well-being. How neutrophils meet their end is physiologically important and can result in different immunologic consequences. Whereas nonlytic forms of neutrophil death typically elicit anti-inflammatory responses and promote healing, pathways ending with cell membrane rupture may incite deleterious proinflammatory responses, which can exacerbate local tissue injury, lead to chronic inflammation, or precipitate autoimmunity. This review seeks to provide a contemporary analysis of mechanisms of neutrophil death. Highlights: Neutrophils are the most abundant immune cells in humans and the first to respond to infection or inflammation. Their rapid generation and secretion of proinflammatory mediators and toxic granular substances require cell death mechanisms to protect against tissue injury. Neutrophil death occurs via diverse pathways regulated by an internal diurnal cell timer, interactions with commensal or pathogenic microorganisms, environmental exposures, as well as cell aging. Neutrophils may undergo apoptosis (less inflammatory), necroptosis, or pyroptosis (both proinflammatory), influencing immune responses and kinetics of disease resolution. Nonapoptotic forms of neutrophil cell death include NETosis or senescence with autophagic degradation of subcellular components. Manipulation of neutrophil death pathways may enable the discoveries of novel therapies to treat certain infectious, autoimmune, and congenital neutrophil disorders.